Perceived stress and risk of any osteoporotic fracture. Issue 6 (June 2016) - Pedersen, A.; Baggesen, L.; Ehrenstein, V.; Pedersen, L.; Lasgaard, M.; Mikkelsen, E.
Abstract Summary Perceived stress is associated with several adverse health outcomes; however, little is known about the impact of stress on fracture risk. In this population-based cohort study, persons with high perceived stress have an increased 5-year risk of any osteoporotic fracture, in particular hip fracture. Introduction We conducted a population-based cohort study in Denmark to examine the association between perceived stress and risk of subsequent osteoporotic fracture. Methods A 2006 population-based health survey in the Central Danish Region (with 1.25 million inhabitants) was used to identify 7943 persons who were 55 years or older on the survey date and completed the Perceived Stress Scale. Individuals were categorized into two groups: high level of stress and low level of stress (including no stress). We obtained information on all osteoporotic fractures through linkage to the Danish National Registry of Patients. We used Cox regression to compute hazard ratios (HRs) with 95 % confidence interval (CI) adjusted for a number of lifestyle factors, socioeconomic data, perceived general health, and prescription history, comparing high- and low-stress persons. Results A total of 1799 persons (22.6 %) reported high level of perceived stress, whereas 6144 (77.4 %) reported low level or no stress. The 5-year risk of any osteoporotic fracture was 7.4 and 5.4 % in persons with high and low perceived stress, respectively, corresponding to adjusted HR of 1.37 (CI 1.00–1.89). The adjusted HR for hip fracture within 5 years associated with high perceived stress was 1.68 (CI 1.04–2.72). The associations weakened with increasing follow-up time. Conclusions Persons with high perceived stress have an increased risk of any osteoporotic fracture, in particular risk of hip fracture within 5 years of stress assessment even after adjusting for differences in lifestyle, comorbidities, osteoporosis presence, medication use, and socioeconomic status at the time of stress level evaluation. The association attenuated after longer follow-up time.